DETERMINANTS OF VOCATIONAL HIGH SCHOOL STUDENTS’ INTENTION TO USE CHATGPT IN LEARNING: INTEGRATING TAM AND UGT - Rismayanti Dwi Indarti; Jaka Nugraha (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2026)
The development of artificial intelligence has influenced learning practices, particularly through the use of ChatGPT as a learning support tool. This study aims to examine the factors influencing students’ intention to use ChatGPT in learning by integrating the Technology Acceptance Model (TAM) and Uses and Gratifications Theory (UGT). The variables analyzed include Perceived Ease of Use, Perceived Usefulness, Convenience, and Information Seeking toward Intention to Use. This study employed a quantitative explanatory approach with respondents consisting of 11th grade students majoring in Office Management. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Generalized Structured Component Analysis (SEM-GSCA). The results indicate that Perceived Ease of Use significantly influences Perceived Usefulness but does not directly affect Intention to Use. Furthermore, Perceived Usefulness and Information Seeking have a significant effect on Intention to Use, while Convenience shows no significant influence. These findings suggest that students’ intention to use ChatGPT is driven more by perceived benefits and information needs than by ease or convenience of use.